2020
DOI: 10.1038/s41598-020-57563-0
|View full text |Cite
|
Sign up to set email alerts
|

Wurtzite AlGaAs Nanowires

Abstract: Semiconducting nanowires, unlike bulk, can be grown in both wurtzite and zincblende crystal phases. this unique feature allows for growth and investigation of technologically important and previously unexplored materials, such as wurtzite AlGaAs. Here we grow a series of wurtzite AlGaAs nanowires with Al content varying from 0.1 to 0.6, on silicon substrates and through a comparative structural and optical analysis we experimentally derive, for the first time, the formula for the bandgap of wurtzite AlGaAs. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 27 publications
1
28
0
1
Order By: Relevance
“…According to our previous works, under the described growth conditions, AlGaA NWs are spontaneously formed by a core-shell structure [24]. Moreover, in the case of nominal Al 0.3 Ga 0.7 A composition, the real content of aluminum in the AlGaAs NW core is 16%, and 24% in the shell [25].…”
Section: Resultsmentioning
confidence: 66%
“…According to our previous works, under the described growth conditions, AlGaA NWs are spontaneously formed by a core-shell structure [24]. Moreover, in the case of nominal Al 0.3 Ga 0.7 A composition, the real content of aluminum in the AlGaAs NW core is 16%, and 24% in the shell [25].…”
Section: Resultsmentioning
confidence: 66%
“…Initiation of branches from adatom accumulation on the NW sidewalls has been reported in the past for other material systems, including GaAs/GaAsBi core/shell NWs 29 and GaSb NWs. 30 Besides, the unintentional formation of Al-rich shell is frequently observed in AlGaAs NWs, 24,[31][32][33][34] and can be established in the NW trunks of the current AlGaAs branched NWs via the radial EDX line scan, which is shown in section 4 of the ESI. † The high density of twins increases the roughness of the shell surface, leading to the formation of concave sites, where Ga preferentially accumulates.…”
mentioning
confidence: 99%
“…It has recently been reported that the WZ form of AlGaAs exhibits a significantly lower direct band gap than the ZB form. 57 With both forms present in a nanostructure, carriers may diffuse into the WZ segments prior to their recombination. The resultant lower PL emission energy would hence lead to a lower calculated effective Al composition, as the ZB band-gap values were used in the calculation.…”
Section: Resultsmentioning
confidence: 99%